The case of the left-handed lady - Springer, Nancy (Springer, Nancy. Enola Holmes mystery., 2008)
Pursued by her much older brother, famed detective Sherlock Holmes, fourteen-year-old Enola, disguised and using false names, attempts to solve the kidnapping of a baronet's sixteen-year-old daughter in nineteenth-century London.